THE NULL SPACES CODIMENSION AND THE EXISTENCE OF THE INTERPOLATING SPLINE-FUNCTION IN BANACH SPACE - Zejnullahu, Ramadan Xh. (Matematichki Bilten, 2000)
Using the results in papers [2] and [3] in this paper we prove the existence of the interpolating spline-function by the null space codimension of operators \(A\) and \(T\).